(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Strengthening the status of the teacher in the Constitution harmonizes the legal norms established in the legal documents in the field of education. The quality of education cannot be improved without raising the status of the teacher. Without improving the quality of education, it is impossible to train qualified specialists. This article describes about the legal status and importance of the teacher’s status in the updated constitution.